IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF - Eka Rohman Yanti; Dewi Yanti; Mansur (UNISAN JURNAL, 2024)
Character education management is very important in the context of education in developing interests, attitudes, and positive behaviors of qualified students in the future. The purpose of the study is to evaluate the impact of implementing character education management and identify effective strategies in achieving positive results. The research method used is qualitative with a single case study design. Data were collected through in-depth interviews with principals, teachers, and students, participant observation, and document analysis. The results showed has successfully implemented character education management by involving all parties and integrating character in the curriculum and school activities. The application of the active, creative, effective and fun learning model (PAKEM) also increases students’ interest and participation in character learning. The character education management approach has succeeded in creating a learning environment that supports the development of students’ interests, attitudes, and positive behaviors. Recommendations for other schools are to strengthen stakeholder engagement, integrate character into the curriculum, and implement the PAKEM learning model in an effort to improve character education. This research makes a valuable contribution to further understanding of the effective application of character education management in school contexts